(untitled) (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2025)
This essay examines the start of the women’s rights movement in post-Revolutionary War America, focusing specifically on Elizabeth Cady Stanton’s Declaration of Sentiments and the ways in which it persuasively paralleled the Declaration of Independence. It highlights the racial exclusions that were inherent in early feminist advocacy, and spotlights the contributions of black women like Sojourner Truth who broadened the movement’s scope while fighting for true inalienable rights for all. By exploring the dynamics of these suffragists and abolitionists, this essay stresses the importance of an intersectional understanding of feminism, both historically and today. For additional context, listen to the author’s reflection on the piece below.